A Journey Through Time and Text: Apostrophe, Literary Memory, and the Human Search for Meaning - Assadi, Jamal (Journal of Ecohumanism, 2025)
This study examines the evolution of apostrophe as a central aesthetic and narrative device across Saul Bellow’s "The Gonzaga Manuscripts," Henry James’s The Aspern Papers, and Bellow’s Humboldt’s Gift. Through a comparative literary approach, the article highlights how Bellow draws on James’s narrative strategies while advancing his distinct exploration of artistic leftover, identity, and existential dilemmas. Apostrophe operates in three transformative phases within these texts: reconciling with the past through nostalgia, enabling self-creation through forward-looking renewal, and establishing meta-literary connections that bridge writers, characters, and readers. In "The Gonzaga Manuscripts," Clarence Feiler’s quest for Gonzaga’s manuscripts reflects a nostalgic longing for coherence in a fragmented identity, mirroring the tensions in James’s The Aspern Papers. This nostalgic engagement evolves in Humboldt’s Gift, where Charlie Citrine reimagines apostrophe as a dynamic act of self-renewal and creativity. By linking these works through their shared aesthetic concerns, the study reveals Bellow’s literary progression and his nuanced engagement with themes of memory, power, and the enduring challenges of artistic and personal hangover.